2015
DOI: 10.1111/cid.12338
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiological Long‐Term Outcome of a Tapered Implant System with Special Emphasis on the Influence of Augmentation Procedures

Abstract: Within the limits of the retrospective character of this study, the tapered soft tissue level implant showed especially in maxillary sinus augmentation promising long-term survival and success rates and a low peri-implant bone resorption compared with the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…2). Schiegnitz et al (2015) found that the tapered design demonstrated direct and indirect advantages in reducing the risk of fracture of the labial cortical plate during all 3 fundamental surgical steps of the split crest technique. Therefore, tapered implants inserted in conjunction with the split crest technique seem to be a promising surgical procedure to treat selected anatomic situations involving insufficient maxillary bone thickness.…”
Section: Implant Shapementioning
confidence: 98%
“…2). Schiegnitz et al (2015) found that the tapered design demonstrated direct and indirect advantages in reducing the risk of fracture of the labial cortical plate during all 3 fundamental surgical steps of the split crest technique. Therefore, tapered implants inserted in conjunction with the split crest technique seem to be a promising surgical procedure to treat selected anatomic situations involving insufficient maxillary bone thickness.…”
Section: Implant Shapementioning
confidence: 98%
“…Dental implant placement is an effective treatment method for the replacement of lost teeth with high survival rates after long-term follow-up [13]. However, the long-term success and stability of implants in function are directly correlated with the quality and quantity of the available bone at the prospective implant site [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical and radiological outcomes of sinus augmentation procedures have been published in several studies [1, 3, 6, 7]. However, little data on the physical and psychological impact of this procedure on the patient is available yet.…”
Section: Discussionmentioning
confidence: 99%
“…Rehabilitation of completely and partial edentulous patients with dental implants has proved to be a safe and predictable procedure [1–3]. However, reduced bone height and the proximity of the maxillary sinus are challenging limitations for dental implant placement in the posterior maxilla [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation